Systematic review and meta-analysis of randomized controlled trials of perioperative outcomes and prognosis of transurethral en-bloc resection vs. conventional transurethral resection for non-muscle-invasive bladder cancer. (August 2022) - Li, Zhouyue; Zhou, Zhongbao; Cui, Yuanshan; Zhang, Yong
Abstract: Objectives: This article aimed to perform a systematic review and meta-analysis of randomized controlled trials (RCTs) of perioperative outcomes and prognosis of transurethral en-bloc resection versus conventional transurethral resection for non-muscle-invasive bladder cancer (NMIBC). Methods: We searched MEDLINE, Web of Science, and the Cochrane Controlled Register of Trials (CENTRAL) to find eligible RCTs. The studies were classified by version 2 of the Cochrane risk-of-bias tool for randomized trials. Review Manager 5.4.0 was used to evaluate the data. The certainty of the evidence was assessed using the Guideline Development Tool by GRADEpro GDT. Results: Seven RCTs with 1142 patients was included in the present study. The results indicated that bladder perforation (OR = 0.17; 95% CI 0.05 to 0.67; P = 0.01), obturator nerve reflex (OR = 0.03; 95% CI 0.01 to 0.13; P < 0.00001), residual tumor (OR = 0.24; 95% CI 0.08 to 0.77; P = 0.02) and repeat transurethral resection of bladder tumor (re-TURBT) (OR = 0.54; 95% CI 0.34 to 0.85; P = 0.008) were significantly reduced in the en-bloc resection group than the conventional resection group. However, there were no significant differences in hemoglobin deficit (p = 0.31), urethral stricture (p = 0.47), and detrusor muscle presence (P = 0.16) between both groups. Besides, resection time (p = 0.25), operative time (p = 0.20), catheter dwell time (p = 0.24), and length of hospital stay (p = 0.16) were similar in the two groups. Meanwhile, en-bloc resection yielded no advantage for the 3-month (P = 0.11), 6-month (P = 0.05), 1-year (P = 0.61), 2-year (P = 0.53), and 3-year (P = 0.26) tumor recurrence rates. Conclusions: Our meta-analysis shows that transurethral en-bloc resection is associated with comparable outcomes to conventional transurethral resection for recurrence-free survival in NMIBC patients. En-bloc resection is more feasible and safer than conventional resection for NMIBC, with fewer intraoperative complications, less residual tumor, and less re-TURBT. Highlights: This is an updated meta-analysis to evaluate en-bloc resection vs. conventional TURBT for non-muscle-invasive bladder cancer. En-bloc resection is comparable to conventional TURBT in recurrence-free survival. En-bloc resection is a more feasible and safer procedure than conventional TURBT for non-muscle-invasive bladder cancer. En-bloc resection does not improve the detrusor muscle presence in the specimen for pathological evaluation.